Strategi Komunikasi Pemasaran Digital Melalui Sosial Media Klinik Sunat Modern Safubot Indonesia - Permata, Sandy (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
The current development of communication technology has changed people’s behavior in obtaining the various information they want and of course also provided the emergence of new ideas and new innovations to simplify the communication process. The use of social media as one of the new media which is currently in contact with life and daily life in all aspects of people’s lives also of course has an impact on the emergence of new knowledge which is also used as a marketing and promotional communication media in various business sectors, including Circumcision Health services. Modern Safubot Indonesia. The aim of this research is to determine marketing communication strategies through social media for health services, especially the Safubot Indonesia Circumcision Clinic. The research method used in this research is a qualitative method with a case study approach. Safubot Indonesia’s marketing communication strategy planning uses social media using three events, namely, Sustain by always continuing to grow and develop by presenting information and communication that intersects with digital media. Second, Open New Market by expanding the branch which is a form of marketing communication which is also carried out through the Instagram branch. And the third is Open New Service with Safubot trying to open other clinics with the main brand Safubot, such as business expansion in the field of other health services. Digital marketing communication activities are carried out using various social media such as websites, Instagram and YouTube, which include advertising content, sales promotions. , direct marketing as well as public relations activities